2017
DOI: 10.1002/jat.3552
|View full text |Cite
|
Sign up to set email alerts
|

Drug interaction at hERG channel: In vitro assessment of the electrophysiological consequences of drug combinations and comparison against theoretical models

Abstract: Drugs carry a proarrhythmic risk, which gets even greater when they are used in combination. In vitro assessment of the proarrhythmic potential of drugs is limited to one compound and thus neglects the potential of drug-drug interactions, including those involving active metabolites. Here we present the results of an in vitro study of potential drug-drug interactions at the level of the hERG channel for the combination of up to three compounds: loratadine, desloratadine and ketoconazole. Experiments were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…We did not observe any pharmacological antagonism or reversal of I hERG block associated with the administration of low concentrations of erythromycin (≤30 µM) with diverse pore and nonpore hERG blockers. However, we did find, consistent with previous reports (Ducroq et al, 2005; Friemel & Zunkle, 2010; Hreiche et al, 2011; Kornick et al, 2003; Margulis & Sorota, 2008; Wiśniowska et al, 2018), that the paired combination of two hERG inhibitors is associated either with independent or additive/synergistic effects. In our hands, pretreatment with erythromycin was associated with either strong synergism (terfenadine, chloroquine), slightly less than additive effects (dofetilide and thioridazine) or limited effects (ketoconazole and BeKm‐1).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We did not observe any pharmacological antagonism or reversal of I hERG block associated with the administration of low concentrations of erythromycin (≤30 µM) with diverse pore and nonpore hERG blockers. However, we did find, consistent with previous reports (Ducroq et al, 2005; Friemel & Zunkle, 2010; Hreiche et al, 2011; Kornick et al, 2003; Margulis & Sorota, 2008; Wiśniowska et al, 2018), that the paired combination of two hERG inhibitors is associated either with independent or additive/synergistic effects. In our hands, pretreatment with erythromycin was associated with either strong synergism (terfenadine, chloroquine), slightly less than additive effects (dofetilide and thioridazine) or limited effects (ketoconazole and BeKm‐1).…”
Section: Discussionsupporting
confidence: 93%
“…Despite the fact that drug‐induced QT interval prolongation often occurs clinically with coadministration of >1 QT interval prolonging drug (Hancox et al, 2008; Yap & Camm, 2003), there are only a few in vitro studies examining the effects of the combined administration of multiple hERG blockers on the hERG channel (e.g., Crumb, 2014; Ducroq et al, 2005; Friemel & Zunkle, 2010; Hreiche et al, 2011; Kornick et al, 2003; Margulis & Sorota, 2008; Wiśniowska, Lisowski, Kulig, & Polak, 2018), and reports on the pharmacological antagonism of hERG block are scarce (Crumb, 2014; Hreiche et al, 2011). Prior to the report of a protective effect of macrolides (Crumb, 2014), one study showed that MAPD 90 ‐ prolongation mediated through I Kr block by the concomitant application of single concentrations of erythromycin or ketoconazole with dofetilide was less than the addition of the effects of each drug alone (Hreiche et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the additional risk of QT prolongation, with some potential combinations of these medications, may be synergistic rather than simply additive. 39 Chloroquine/hydroxychloroquine, the antimalarial agents that potentially block infection by increasing the endosomal pH required for virus/cell fusion, and lopinavir/ritonavir, protease inhibitors that interfere with the virus RNA replication, are 2 common culprits. Notably, in both cases, the impact on ventricular repolarization is direct, via inhibition of the hERG-K+ channel, and also indirect by increasing circulating levels of other concomitant QT-prolonging drugs.…”
Section: Drug Therapymentioning
confidence: 99%
“…Loratadine and desloratadine block cloned hERG channels in mammalian cells with much lower potency than terfenadine (330 nM), with estimated IC 50 values of about 5000-100000 nM for the former and 1950 nM for the latter. 44,45,73,74 These IC 50 values are more than 300 times higher than the maximal plasma concentration attained by loratadine and desloratadine after a single administration of the recommended daily doses of 10 and 5 mg, respectively. [75][76][77] Importantly, C max values were more than 100 times lower than hERG IC 50 values when loratadine or desloratadine was updosed twofold or fourfold [75][76][77] (Table 1).…”
Section: Loratadine and Desloratadinementioning
confidence: 99%